(3MdjI GdaQSGf hTYGQ GdTLYGfs - (3eMeO Hf eMeO Hf Ydj Hf CMeO Hf GdfMGS GdbjSjs
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HGdEjeGf CeG HYO cJH Gddg GdfUQ GdeDjO ddebGe GdcHjQ CHj GdMLGL Hf jhSa s
(3BNQgG (B:s
(3LGd GdZHWI dOjI hGHSW HGdNjQGJ jOjg Gfc Ydi cd TF bOjQ hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(280(3c(B) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs